Analyzing the economics of food loss and waste reductions in a food supply chain. (January 2021) - de Gorter, Harry; Drabik, Dušan; Just, David R.; Reynolds, Christian; Sethi, Geeta
Highlights: We produce a general analytical framework for food waste in the food supply chain. Our model highlights the potential conflicts between food policy goals. Cuts in consumer food waste are not always more beneficial than at producer level. Effectiveness depends on cascading effects, costs and waste distribution rates. Careful analysis is needed for each country- and commodity-specific context. Abstract: The paper provides an economic model of food waste for consumers, intermediaries and farmers based on first principles. We distinguish between purchases and sales for each intermediary, purchases and consumption for consumers, and gross production versus sales for farmers. Because of waste at each stage of the supply chain, agents need higher sales prices to compensate. Our model is able to make more accurate predictions of how interventions (public policies or private initiatives) designed to reduce food waste influence the markets overall, including indirect (cascading) effects. We show the uniqueness of these interaction effects with a formal model and simulate an empirical model calibrated to market parameters and rates of waste for two commodities (chicken and fruit) in the UK. We show that the impacts of reducing waste vary by commodity, depending on supply and demand elasticities, degree of openness to international trade and the initial rates of food loss and waste at each stage of the value chain. The cascading effects up and down the supply chain mean that in some cases interventions to reduce food waste will be reinforced while in other cases partially offset.